Akkermansia muciniphila supplementation prevents cognitive impairment in sleep-deprived mice by modulating microglial engulfment of synapses - Na Li; Shuwen Tan; Yue Wang; Jiao Deng; Nan Wang; Shan Zhu; Wen Tian; Jing Xu; Qiang Wang (Gut Microbes, 2023)
ABSTRACTThe microbiome-gut-brain axis plays a crucial role in many neurological diseases, including mild cognitive impairment. Sleep deprivation (SD) induces cognitive decline accompanied by alterations in the gut microbiota. However, the role of gut microbiota alterations in SD-induced cognitive dysfunction and the underlying mechanisms remain unclear. Here, we found that dysbiosis of the gut microbiota following pretreatment with broad-spectrum antibiotics worsens SD-induced cognitive impairment in mice. Fecal microbiota transplantation from SD mice to healthy mice induced cognitive impairment. Additionally, the abundance of Akkermansia muciniphila (A. muciniphila) in the mouse gut microbiota was significantly reduced after 7 days of SD. A. muciniphila pretreatment alleviated cognitive dysfunction and prevented synaptic reduction in the hippocampus in SD mice. A. muciniphila pretreatment inhibited extensive microglial activation and synaptic engulfment in the hippocampus of SD mice. Metabolomics analysis revealed that A. muciniphila pretreatment increased the serum acetate and butanoic acid levels in SD mice. Finally, pretreatment with short-chain fatty acids (SCFAs) inhibited microglial synaptic engulfment and prevented neuronal synaptic loss in SD mice and primary microglia-neuron co-culture following LPS stimulation. Together, our findings illustrate that gut dysbiosis plays an essential role in SD-induced cognitive impairment by activating microglial engulfment at synapses. A. muciniphila supplementation may be a novel preventative strategy for SD-induced cognitive dysfunction, by increasing SCFAs production and maintaining microglial homeostasis.